Almonds as an energy source in endurance exercise - Esquius, L.; Nino, O.; Alamo, J.; Javierre, C. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
Several studies have investigated the effects of fat feeding before exercise on the subsequent rates of substrate oxidation and exercise performance. Some results revealed that unsaturated fatty acids supplementation tended to slightly increase fat oxidation. However, these changes were not reflected in VO2max or in other performance and physiological parameters. We selected almonds as a source of fatty acids to make an acute fat supplementation. Almonds, by weight, are about 50% lipids, mostly monounsaturated fatty acids, which could be an energetic substrate. We made an original almond product (almond supplement) and investigated its effects on nonesterified fatty acids (NEFA) values and exercise performance. The almond supplement`s main ingredients were almonds and the placebo supplement`s main ingredient was bread. Five male and trained subjects went through two separate cycling effort test sessions separated by 7-day interval. The supplements were taken two hours before the test. Several blood samples were collected before, during and after testing for biochemical measurements. The results showed a NEFA increase of 0.09 mg·dL-1 (95% CI = 0.05-0.14) (p < 0.0001) during the test in those taking the almond supplement in comparison to those taking the placebo. Almonds supplementation enhanced performance in comparison to placebo (almonds supplementation 5389 ± 1795 w vs. placebo 4470 ± 2053 w, p = 0.043). This supplementation rich in fatty acids did not show gastrointestinal disturbances. Our study suggests that an acute almond supplementation taken two hours before exercise can improve performance in trained subjects.